A Solid Waste Pond Tiger Shrimp (Peneaus monodon) as Fertilizer for Caulerpa lentillifera - Saputra, Nyoman Robby Manik; Sukoso, Sukoso; Kartikaningsih, Hartati (Graduate School, Universitas Brawijaya, 2017)
Farming the shrimp, fish and another commodity could produce large quantities of waste. Aquaculture waste can be formed as feces, residual feed and dead organism which are accumulated in a cultivation area. Generally, the waste is discharged directly into the water without filtration. Thus, one of the problems that are often faced by farmer is the low quality of pure water due to the high content of nutrients. Moreover, suspended solid pollutant will be formed that lead to eutrophication, oxygen depletion, and precipitation. The aim of this research is to analyze the solid waste pond tiger shrimp as fertilizer for the growth of Caulerpa lentiilifera. Here, the Random Design complete (RAL) and three times in Deuteronomy are used in the experiment. The parameters of one control and three treatment doses are used 0, 2, 4, and 6 g.L-1 respectively. The results showed that solid waste shrimp ponds can be used as fertilizer to meet the needs of Caulerpa lentillifera for growth and the results show the highest value is found in the dose of 6 g.L-1 with NO3- (4.58 ppm), NH4+ (3.34 ppm), PO43- (2.03 ppm) and the value of the rate of growth and the PH are obtained (3.64 g.day-1) and (6,4-8), respectively. Keywords: Caulerpa lentillifera, growth rate, Nitrification, solid waste, Tiger Shrimp.